1962
DOI: 10.1080/00268976200100251
|View full text |Cite
|
Sign up to set email alerts
|

The optical and electron resonance spectra of SO3-

Abstract: The ionic radical SO3-has been identified in T-irradiated single crystals of sodium dithionate, sulphamic acid, potassium sulphamate, potassium amine disulphonate and potassium methane disulphonate. The electron resonance spectrum is a single line with an isotropic g factor of 2"004. The principal values of the ~3S hyperfine coupling tensor are 428, 314 and 316 Mc/s, from which the percentages of 3s and 3p character of the unpaired electron orbital are obtained, enabling a value of 111 ~ for the O-S-O angle to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

1969
1969
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(51 citation statements)
references
References 11 publications
3
48
0
Order By: Relevance
“…The principal values of the 33S03-A-tensor are given in Table 1 and agree very well with those reported by Chantry et al (10). The tensor shows cylindrical symmetry and all three elements must have the same sign, otherwise the atomic 33S anisotopic coupling (2B) of 56 G would be exceeded.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The principal values of the 33S03-A-tensor are given in Table 1 and agree very well with those reported by Chantry et al (10). The tensor shows cylindrical symmetry and all three elements must have the same sign, otherwise the atomic 33S anisotopic coupling (2B) of 56 G would be exceeded.…”
Section: Resultssupporting
confidence: 88%
“…In the present study at high gain and modulation amplitude the four weak isotopic lines due to 33S03-in 0.76% natural abundance were observed. The same downfield shift of the 33S hyperfine pattern relative to the single line of the 32S spectrum was found as that reported by Chantry et al (10). This effect is expected if second order terms are retained in the derivation of the line positions from the spin Hamiltonian (12).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The unpaired spin on S03 has been c culated to be 62% on the sulfur and 13% on each of t oxygens (55,56). SO3-can be considered, therefore, a sulfur-centered radical.…”
Section: Formation and Detection Of S03-radicalsmentioning
confidence: 99%
“…Chantry et al (1) found a single absorption line with a g value of 2.004 in the e.s.r. spectra of gamma irradiated single crystals of sodium dithionate.…”
Section: Introductionmentioning
confidence: 98%